The role of soft skills in employability in the financial industry - Lorenzo Constantino; Jacek Rodzinka (Financial Internet Quarterly, 2022)
The purpose of this article is to present and analyze the results of research on soft skills that in- crease employability in the financial sector. The article presents not only a diagnosis of the im- portance of soft skills in the banking and financial industry, but also indicates which soft skills may be poised to increase employability, which skills are lacking among new entrants in the job market of the banking and financial industry, and how soft skills training is perceived among in- dustry participants. Finally, the importance of these variables in the banking and financial indus- try has been compared with their importance in other industries.
Keywords: J21; J24; G20; G40; 330; soft skills; finance; employability; financial industry